The Development of Collaborative-Based Learning Models to Increase Self-Efficacy and Positive Attitudes of Primary Teacher Education Students towards Inclusive Education in Yogyakarta - Wati, Unik Ambar; Hermanto, Hermanto; Rahmadonna, Sisca; Pujaningsih, Pujaningsih; Komalasari, Mahilda Dea; Pratama, Kukuh Wahyudin (Jurnal Prima Edukasia, 2023)
This study attempts to develop a collaborative-based learning model that can increase self-efficacy and positive attitudes of Primary Teacher Education (PGSD) students toward inclusive education in Indonesia. This study is intended to provide an understanding to PGSD students who are also teacher candidates. The understanding is about the importance of positive attitudes and teaching abilities, which in this study are limited in self-efficacy. The present study employed the Research and Development (R & D) research model. The research participants were elementary school teachers who teach in inclusive schools and 54 PGSD students. Quantitative and qualitative techniques were used to analyze the data. Mann–Whitney U test was used to determine changes in students' self-efficacy and attitudes before and after learning activities. The results indicate a significant difference in self-efficacy with p sig < 0.05. The t-test result is 0.119. As the tcount is greater than the ttable (0.119 > 0.05), it indicates that there is no significant difference. Hence, it can be inferred that there is no statistically significant difference in developing a collaborative-based lecture model aimed at enhancing self-efficacy and fostering favorable attitudes among PGSD students towards inclusive education in Yogyakarta.